Aprendizaje invertido como una aplicación del modelo de m-learning - Cesar Augusto Hernández-Suárez; Carlos Antonio Pabón-Galán; Luisa Stella Paz-Montes (Mundo Fesc)
The objective was to analyze the effect of flipped learning as an application of the m-learning model on the metacognitive thinking skills of higher education students. This study was an experimental study involving 34 university students from a natural sciences teacher training program in Cúcuta, Colombia, divided into an experimental and a control group. A pretest and posttest were used to measure the students' level of metacognitive thinking. The data were analyzed using an independent samples t-test to examine the significant differences between the students' mean scores on the posttest. The results showed that students in the experimental group successfully outperformed those in the control group on the posttest, in addition to a significant difference between the pretest and posttest scores of students in the experimental group. Flipped learning, based on the m-learning model, is an innovative model for improving the educational process and the level of metacognitive thinking. The results provide insight into the flipped classroom as an alternative educational approach in higher education.